PELUANG DAN TANTANGAN PERKULIAHAN DARING DI STIT AL-FATTAH SIMAN LAMONGAN TAHUN 2020 - Muhammad Sya'roni (PUSAT PENELITIAN DAN PENGABDIAN MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2020)
In any situation and condition, the wheel of the tridharma of higher education must continue to run. In the midst of the COVID-19 pandemic, STIT Al-Fattah Siman Lamongan is required to keep going with the various opportunities and challenges. The COVID-19 pandemic requires the emergence of government policies for online lectures. This research will reveal the opportunities and challenges faced by STIT Al-Fattah Siman Lamongan in online lectures. The research approach used is a qualitative approach with the interview and questionnaire data collection methods. The results showed that the chances of online lectures were very high as evidenced by the availability of the necessary facilities. The challenges faced are the low level of student understanding of the lecture material